Existence domain of electrostatic solitary waves in the lunar wake - Rubia, R.; Singh, S. V.; Lakhina, G. S. (My University, 2018)
Electrostatic solitary waves (ESWs) and double layers are explored in a four-component plasma consisting of hot protons, hot heavier ions (HeÃ¾Ã¾), electron beam, and suprathermal electrons having j-distribution using the Sagdeev pseudopotential method. Three modes exist: slow and fast ion-acoustic modes and electron-acoustic mode. The occurrence of ESWs and their existence domain as a function of various plasma parameters, such as the number densities of ions and electron beam, the spectral index, j, the electron beam velocity, the temperatures of ions, and electron beam, are analyzed. It is observed that both the slow and fast ion-acoustic modes support both positive and negative potential solitons as well as their coexistence. Further, they support a â€œforbidden gap,â€ the region in which the soliton ceases to propagate. In addition, slow ion-acoustic solitons support the existence of both positive and negative potential double layers. The electron-acoustic mode is only found to support negative potential solitons for parameters relevant to the lunar wake plasma. Fast Fourier transform of a soliton electric field produces a broadband frequency spectrum. It is suggested that all three soliton types taken together can provide a good explanation for the observed electrostatic waves in the lunar wake.
Keywords: Electrostatic solitary waves; Lunar wake; Sagdeev pseudopotential method